1999
DOI: 10.1128/jcm.37.7.2280-2284.1999
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Pseudoepidemic Caused by Bacillus cereus Traced to Contaminated Ethyl Alcohol from a Liquor Factory

Abstract: From September 1990 to October 1990, 15 patients who were admitted to four different departments of the National Taiwan University Hospital, including nine patients in the emergency department, three in the hematology/oncology ward, two in the surgical intensive care unit, and one in a pediatric ward, were found to have positive blood (14 patients) or pleural effusion (1 patient) cultures for Bacillus cereus. After extensive surveillance cultures, 19 additional isolates of B. cereus were recovered from 70% eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Bacillus anthracis causes anthrax and represents one of the most molecular monomeric bacteria known. Jackson et al (1997) reported that PCR analysis of 198 B. anthracis isolates revealed a variable region of the vrrA gene sequence, which resulted in ®ve polymorphisms among isolates. In vrrA±RFLP analysis, the unique restriction digestion pattern in all but one strain of B. anthracis con®rmed the clonal nature of this species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacillus anthracis causes anthrax and represents one of the most molecular monomeric bacteria known. Jackson et al (1997) reported that PCR analysis of 198 B. anthracis isolates revealed a variable region of the vrrA gene sequence, which resulted in ®ve polymorphisms among isolates. In vrrA±RFLP analysis, the unique restriction digestion pattern in all but one strain of B. anthracis con®rmed the clonal nature of this species.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the need for new, fast and reproducible tools to improve our knowledge of relatedness with B. cereus group bacteria, suitable genes for genotype typing schemes were investigated. The VNTR region located in the B. anthracis vrrA gene sequence can separate all known B. anthracis strains into ®ve categories (Jackson et al 1997). It has also been reported that B. cereus and B. mycoides vary from B. anthracis isolates by 158and 170-nucleotide differences, respectively (Andersen et al 1996).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A pseudo-outbreak was reported due to contamination of ethanol with spores of B. cereus. The ethanol was used in the hospital pharmacy for preparation of skin antiseptics without spore filtration (219). Another report described contamination of 70% ethanol with spores of Clostridium perfringens, which was eliminated by addition of 0.27% hydrogen peroxide over 24 h (602).…”
Section: Ethanol Isopropanol and N-propanolmentioning
confidence: 99%